2016
DOI: 10.1051/e3sconf/20160911013
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate size effect on the water retention properties of a lime-treated compacted silt during curing

Abstract: Abstract.The main drying paths of the water retention curves of lime-treated soils were measured. Aggregate size effect on the water retention property was emphasised. Four soil powders with different maximum aggregate sizes (Dmax = 5, 2, 1 and 0.4 mm) were prepared and mixed with 2% quicklime (by weight of dry soil). Samples were prepared by static compaction at dry side of optimum water content (w = 17%) with a dry density of 1.65 Mg/m 3 .Suction measurement was performed by a dew-point hygrometer at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results showed that after one year of curing, the C-S-H phase in the form of tobermerite was detected in the treated soil provided with the coarse aggregates. However, the C-S-H phase was not detected in the treated soil provided with the fine aggregates by XRD analysis and was also too small to be detected using MIP [15].…”
Section: Introductionmentioning
confidence: 91%
“…The results showed that after one year of curing, the C-S-H phase in the form of tobermerite was detected in the treated soil provided with the coarse aggregates. However, the C-S-H phase was not detected in the treated soil provided with the fine aggregates by XRD analysis and was also too small to be detected using MIP [15].…”
Section: Introductionmentioning
confidence: 91%